In Vitro Propagation of Groundnut (Arachis hypogea L.) - Al-Joboury, Kh. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A protocol has been developed for micropropagation of Arachis hypogea L. under in vitro conditions. Nodal explants gave rise to multiple shoots when cultured on MS medium supplemented with different concentrations of BA (benzyladenine) with Kin (Kinetin) or GA3(gibberellic acid). The highest response of shoot multiplication was obtained in MS containing 1.5 mg.l¯¹ BA and 0.5 mg.L¯¹ Kin. The regenerated shootlets were rooted on MS(Murashige and Skoog) basal medium with different concentrations of IBA (indolbutyric acid) and IAA (indol acetic acid). The highest response of rooting was achieved with IBA at 0.05 + IAA at 0.05 mg.L¯¹. The maximum frequency of rooting and highest number of roots were produced on medium containing IBA 0.05 mg.L¯¹ and IAA 0.05 mg.L¯¹. The plantlets, thus successfully established in soil.